Heat distribution when titanium alloy vt9 grinding - Dusan Steklac; Miroslav Neslusan (Communications - Scientific letters of the University of Zilina, 2000)
Heat distribution in machining is one of phenomenological characteristics of this process because it significantly influences functional properties of machined surfaces. The paper deals with heat distribution in the cutting zone when grinding titanium alloy VT9 based on experimental measurement of surface temperature and tangential component of cutting force. Heat distribution when grinding titanium alloy VT9 differs from heat distribution when grinding conventional roll bearing steel 14 209.4 as a typical representative of ground hardened steels first of all because of low heat conductivity of titanium alloys.